2022
DOI: 10.1021/acs.est.2c02934
|View full text |Cite
|
Sign up to set email alerts
|

Daily Local-Level Estimates of Ambient Wildfire Smoke PM2.5 for the Contiguous US

Abstract: Smoke from wildfires is a growing health risk across the US. Understanding the spatial and temporal patterns of such exposure and its population health impacts requires separating smoke-driven pollutants from non-smoke pollutants and a long time series to quantify patterns and measure health impacts. We develop a parsimonious and accurate machine learning model of daily wildfire-driven PM 2.5 concentrations using a combination of ground, satellite, and reanalysis data sources that are easy to update. We apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(154 citation statements)
references
References 81 publications
(145 reference statements)
7
109
1
Order By: Relevance
“…Studies using data prior to 2016 concluded that the wildfire contribution to measured PM 2.5 concentrations was apparent mainly in the northwest of the contiguous US (CONUS), but disagreed over whether enhancements in this region were observable in average annual concentrations or only in extreme daily concentrations (5,6). Studies that include more recent data from the very active 2018 and 2020 wildfire seasons conclude that the imprint of wildfire smoke on surface average and extreme PM 2.5 concentrations has expanded substantially in geographic scope, with observed enhancements throughout much of the Western US (7,8). Research also suggests that wildfire smoke is increasingly implicated in "exceptional event" designations, or days on which regulators exempt observed pollutant concentrations from determination of regulatory attainment under the Clean Air Act because the source of the pollution was deemed beyond control of local authorities (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using data prior to 2016 concluded that the wildfire contribution to measured PM 2.5 concentrations was apparent mainly in the northwest of the contiguous US (CONUS), but disagreed over whether enhancements in this region were observable in average annual concentrations or only in extreme daily concentrations (5,6). Studies that include more recent data from the very active 2018 and 2020 wildfire seasons conclude that the imprint of wildfire smoke on surface average and extreme PM 2.5 concentrations has expanded substantially in geographic scope, with observed enhancements throughout much of the Western US (7,8). Research also suggests that wildfire smoke is increasingly implicated in "exceptional event" designations, or days on which regulators exempt observed pollutant concentrations from determination of regulatory attainment under the Clean Air Act because the source of the pollution was deemed beyond control of local authorities (9).…”
mentioning
confidence: 99%
“…To isolate the contribution of wildfire smoke to pollution concentrations, we build on earlier work (6,8) and use a combination of ground-and satellite-based measurements to isolate the component of surface PM 2.5 concentrations attributable to wildfire smoke. Specifically, our primary analysis combines daily data from thousands of regulatory pollution monitoring stations from across the US with satellite-and analyst-based estimates of when and where wildfire smoke is in the air (Fig S1).…”
mentioning
confidence: 99%
“…We also take two steps to explore whether the source of air pollution influences its impact on political participation. First, we leverage new data on particulate matter emissions from wildfires (Childs et al 2022). Pollution from wildfires may be especially likely to shape people's willingness to take political action.…”
Section: Sources Of Air Pollutionmentioning
confidence: 99%
“…Given decades of successful air pollution regulations coupled with the dramatic increase in fire activity across the western United States (Abatzoglou and Williams, 2016), smoke particulate matter (PM2.5) from wildfires presents one of the greatest threats to air quality in the United States, especially in the West (Childs et al, 2022;Larsen et al, 2018). PM2.5 can penetrate deep into the lungs, leading to an array of health effects, including pulmonary disease, stroke, and premature death (Landguth et al, 2020;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%